Analisis Implementasi Akad Qardhul Hasan Terhadap Peningkatan Pendapatan Penerima Manfaat - Puri Rohmatullah (STAI La Tansa Mashiro, 2023)
Non-bank financial institutions are an alternative form for business actors in finding solutions to meet the need for additional capital, the mechanism of which is not onerous and relatively easy. The Amil Zakat Harapan Dhuafa Institute is an institution that provides an alternative by providing capital assistance in the form of a Qardhul Hasan contract. This study was to analyze the effect of the qardhul hasan contract program on increasing beneficiary income. The method used is quantitative, measured using several indicators, namely increased income, operating profit, and increased consumers. Based on the results of the study, it was shown that the lending program using the qardhul hasan contract had a positive and significant effect on increasing the income of beneficiaries in the city of Serang with the results of the t-count test which showed that the t-count value was 5.014 > from t-table, which was 2.160. So that the Qardhul Hasan Agreement affects the Increase in Beneficiary Income.Keywords: Qardhul Hasan Contract, Increased Income